Implementasi Metode Cooperative Learning Type Jigsaw Dalam Meningkatkan Kualitas Belajar Mata Pelajaran Fiqih di MA Darussalam Ngesong Sengon Jombang - Moch Abdullah Roghib; Aida Arini (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This research is motivated by the low quality of Fiqh learning at MA Darussalam Ngesong Sengon Jombang which is caused by the use of conventional learning methods such as lectures that tend to be monotonous. In the context of Islamic education, Fiqh has an important role as a basis for understanding sharia law. Therefore, innovation in learning methods is needed that can increase motivation, active participation, and student learning outcomes. One of the alternatives used in this study is the Jigsaw type Cooperative Learning method.The focus of this research covers three things: (1) How is the implementation of the Cooperative Learning Type Jigsaw method at MA Darussalam Ngesong Sengon Jombang. (2) How is the quality of learning the Fiqh subject at MA Darussalam Ngesong Sengon Jombang. (3) How is the implementation of the Cooperative Learning Type Jigsaw method in improving the quality of learning in the Fiqh subject at MA Darussalam Ngesong Sengon Jombang.This research employs a qualitative descriptive approach using a case study method. Data collection techniques include observation, interviews, and documentation. The informants in this study consist of Fiqh teachers, the principal, and students.The results of the study (1) The implementation of the Cooperative Learning Jigsaw Type at MA Darussalam Ngesong Sengon Jombang consists of three stages, namely the preparation of group formation, the distribution of learning material tasks, and reflection and feedback. (2) The quality of learning in the Fiqh subject at MA Darussalam Ngesong Sengon Jombang is assessed through three main aspects: conceptual understanding, learning independence, as well as motivation and enthusiasm. (3) The implementation of the Cooperative Learning Jigsaw Type method in improving the quality of learning in the Fiqh subject at MA Darussalam Ngesong Sengon Jombang focuses on three areas: understanding of basic fiqh material, knowledge of worship practices, and the application of purification laws